Strategi fundraising zakat profesi pada organisasi pengelola zakat (OPZ) di Kabupaten Jepara - Aan Zainul Anwar; Evi Rohmawati; Miftah Arifin (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to determine the strategy of zakat organization (amil zakat institution) in Jepara Regency on professional zakat fundraising as well as constraints and challenges in managing professional zakat collection. This study used a qualitative method of case study with validity testing of source triangulation. Data was obtained through interviews with respondents from the leadership of Baznas, NU-Care Lazisnu and Lazismu, Jepara district, and the community who channeled their profession's zakat through the institution. The results of this study show that one of the main strategies in professional zakat collection in Jepara Regency is mapping potential muzakki, transparency and maintaining muzakki loyalty. The main obstacle for the community is not yet fully aware of professional zakat, so the challenge of fundraising professional zakat is to give an understanding that is not only fiqh but also regulation.